Results in the Latin America and Caribbean Region, 2015, Volume 6 - World Bank (World Bank, Washington, DC, 2016)
Latin America and the Caribbean (LCR) will be center stage in the global development debate as leaders from around the world convene in Lima, Peru for the annual meetings of the World Bank Group and International Monetary Fund. Critical progress in poverty reduction has been made in the region over the last decade. The region’s bottom 40 percent of the population saw growth eclipsing that seen by the group in every other region in the world. However, a global slowdown in economic growth and activity challenges these positive strides. The stories in this report embody concrete successes of countries working together with the World Bank. Innovative development approaches were designed and implemented. Individuals, communities, countries, and even regions benefited from better health, education, governance, disaster risk management, and more.